Eu te amo – a song by Tom Jobim and Chico Buarque - Carmo Jr., José Roberto do (Laboratório Editorial FCL-UNESP, 2008)
This essay analyses Chico Buarque's and Tom Jobim's song by taking into account the work of both the poet and the musician as a way to create an array of compatibilities between lyrics and melody. The lyrics are presented as a passionate text paradoxically woven with so called quasi-logic arguments (Perelman), whereas for the melody the waltz genre as well as the rondo and the harmonic circularity are some of the elements found in resonance with Chico Buarque's lyrics.